Progress in understanding conversion disorder - Allin, Matthew (Dove Medical Press, 2005)
Conversion disorder has a history that may reach back into antiquity, and it continues to present a clinical challenge to both psychiatrists and neurologists. This article reviews the current state of knowledge surrounding the prevalence, etiology, and neurobiology of conversion disorder. There have been improvements in the accuracy of diagnosis that are possibly related to improved technologies such as neuroimaging. Once the diagnosis is made, it is important to develop a therapeutic alliance between the patient and the medical team, and where comorbid psychiatric diagnoses have been made, these need to be adequately treated. While there have been no formal trials of medication or psychoanalytic treatments in this disorder, case reports suggest that a combination of antidepressants, psychotherapy, and a multidisciplinary approach to rehabilitation may be beneficial.